Investigations on the mechanism of microweld changes during ultrasonic wire bonding by molecular dynamics simulation. (July 2020) - Long, Yangyang; He, Bo; Cui, Weizhe; Ji, Yuhang; Zhuang, Xiaoying; Twiefel, Jens
Abstract: Despite the wide and long-term applications of ultrasonic (US) wire bonding and other US metal joining technologies, the mechanism of microweld changes during the bonding process, including formation, deformation and breakage, is rarely known as it is very difficult to be investigated by experiments. In this work, this mechanism under different surface topographies and displacement patterns is studied by molecular dynamics simulation. It is found that microwelds can be formed or broken instantly. Due to the relative motion between the local wire part and the local substrate part, microwelds can be largely deformed or even broken. The impacts of material, surface topography, approaching distance and vibration amplitude on the microweld changes are investigated via the quantification of the shear stress and the equivalent bonded area. It is shown that these four factors significantly influence the final connection and the interface structure. The analysis of the scale influence on the microweld changes shows that the simulation results at a small-scale are able to represent those at a large-scale which is close to the range of the commonly used surface roughness. This deeper understanding on the microweld changes leads to a better control strategy and an enhancement of the bonding process. Graphical abstract: Unlabelled Image Highlights: The mechanism of microweld formation and breakage was studied for the first time. The mechanism of microweld changes under different configurations was investigated. The significant impact factors on microweld changes were analyzed. A large deformation and a middle-level amplitude are helpful for microweld growth.